Proceedings of the Joint International Conference on Measurement and Modeling of Computer Systems 2006
DOI: 10.1145/1140277.1140296
|View full text |Cite
|
Sign up to set email alerts
|

On suitability of Euclidean embedding of internet hosts

Abstract: In this paper, we investigate the suitability of embedding Internet hosts into a Euclidean space given their pairwise distances (as measured by round-trip time). Using the classical scaling and matrix perturbation theories, we first establish the (sum of the) magnitude of negative eigenvalues of the (doubly-centered, squared) distance matrix as a measure of suitability of Euclidean embedding. We then show that the distance matrix among Internet hosts contains negative eigenvalues of large magnitude, implying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 8 publications
(10 reference statements)
1
52
0
1
Order By: Relevance
“…This figure confirms the finding in [16], in that the errors do increase significantly for estimating shorter distances (note the logarithmic scale on Y-axis) for all methods. For example, the median relative error of distance prediction of GNP for real distance between 100 and 1000 milliseconds is just under 10%, but it increases to 68% for real distances below 10ms.…”
Section: Accuracy By Distance Rangessupporting
confidence: 88%
See 3 more Smart Citations
“…This figure confirms the finding in [16], in that the errors do increase significantly for estimating shorter distances (note the logarithmic scale on Y-axis) for all methods. For example, the median relative error of distance prediction of GNP for real distance between 100 and 1000 milliseconds is just under 10%, but it increases to 68% for real distances below 10ms.…”
Section: Accuracy By Distance Rangessupporting
confidence: 88%
“…As future work, we would like to investigate some optimizations to our approach we mentioned throughout the paper, most notably, accounting for triangle shape during dynamic triangle selection and using a replacing the triangle with a single landmark when it is particularly close to one of the end hosts. We would also like to combine our approach with some orthogonal techniques that have been proposed to enhance distance estimation and measurement [15,16].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in reality, the triangle inequality is often violated due to the Internet's structure and routing policies. In [7,8,9,10], it has been shown that the violations of triangle inequality (TIVs) in the Internet delay space are not rare and that their impacts on ICS are not negligible. Indeed, a TIV indicates the existence of a shorter path from the source node to the destination node via an intermediate node than a direct path.…”
Section: Introductionmentioning
confidence: 99%